ARE THESE TWO VIEWS ABOUT NEW REPRODUCTIVE TECHNOLOGIES CONTRADICTORY? - Terence Rajivan Edward, (IJRDO - Journal of Social Science and Humanities Research, 2024)
This paper responds to two seemingly contradictory views that anthropologist Jeanette Edwards identifies in an article on the impact of new reproductive technologies in the northwest of England. I argue that they are probably not contradictory. But I do so by modifying how the views are formulated and reflect on the significance of this for the aim of accessible anthropology at home